Fault-tolerant cooperative control for multiple UAVs based on sliding mode techniques - Li, Peng; Yu, Xiang; Peng, Xiaoyan; Zheng, Zhiqiang; Zhang, Youmin (Science China. Information sciences, 2017)
This paper proposes a fault-tolerant cooperative control（FTCC） design approach for multiple unmanned aerial vehicles（UAVs）, where the outer-loop control and the inner-loop fault accommodation are explicitly considered. The reference signals for the inner-loop of the follower UAV can be directly produced by resorting to a proportional control. In the presence of actuator faults, the estimation of the fault information can be completed within finite time. Moreover, the control of the inner-loop is reconfigured based on the fault information adaptation and sliding mode techniques, such that the deleterious effects due to failed actuators can be compensated within finite time. Simulations of UAV cooperative flight are conducted to illustrate the effectiveness of this FTCC scheme.